i need to simplify this.

## what is the answer to -6(x+9)

Tutors, please sign in to answer this question.

# 3 Answers

If expression was actually worded equal to zero the solution is as follows

-6(x+9)= 0

-6x + -6*9= 0 expand the left side

-6x + -54 = 0 calculate expressions inside left side

x + 9 =0 divide both sides by -6

x = -9 solution

CHECK: -6(x+9)= 0 @ x= -9 => -6(-9 + 9) = 0 correct because -9 +9 = 0 & -6*0=0

To simplify, you need to distribute the -6 through to the expression within the parentheses.

-6(x+9)=

-6(x) + -6(9)= -6x-54

This is the only way to really simplify the expression you gave.

Using the distributive property, the -6 is multiplied by x and also multiplied by 9: (-6)(x) + (-6)(9) = -6x -54

## Comments

thank ya'll so much

Comment